Comparison of the methods of intracorporeal knot and hem-o-lok clip to cover the stumps in laparoscopic appendectomy (Annals of Medical Research, 2021)
None
Keywords: Acute Appendicitis; Appendix Stump; Laparoscopic Appendectomy.br /